The Colonialism and Stereotypes Based on Race and Religion: Representation of Papua in Indonesian Elementary Textbook School - Radius Setiyawan; Maulida Maulida (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2024)
Implementing anti-racist pedagogy in Islamic schools, particularly for Muslim teachers, involves unique challenges. Their behaviour is closely scrutinized, making it crucial to emphasize positive Islamic behaviour, including antiracism efforts, to contribute to a more just society. This research explained the root of racism and equality in Islam. In addition, this research add explanation on how Islamic education has significant role as well as antiracism paedagogy through school text book. School textbooks are effective media for conveying educational messages or values to children. Besides being made as an educational medium, books are also deliberately designed to represent the ideal interests according to their creator, especially books published by the state. The content can undoubtedly describe what is suitable for each country. Through school textbooks, we can look at the state's perspective on ethnicity critically. Based on this, this study will describe the representation of an ethnic group, especially the Papuan ethnic group. This research is not only limited to the study of texts but will try to do interdiscussion with the existing social context. By using Critical Discourse Analysis (CDA) this research will provide a complete picture of how the text is formed and what discourses are present in the formation of the text. The text in this study consisted of 2 related types, namely picture text and narrative text. In addition, this research is necessary because the findings will provide an overview of the content of school textbooks related to how regional representation is described. This is important to note as one of the instruments to build contemporary Indonesian identity especially in the national and Islamic education sector.